Effects of Alkyl Terminal Chains on Morphology, Charge Generation, Transport, and Recombination Mechanisms in Solution‐Processed Small Molecule Bulk Heterojunction Solar Cells. Issue 17 (18th June 2015) - Min, Jie; Luponosov, Yuriy N.; Gasparini, Nicola; Richter, Moses; Bakirov, Artem V.; Shcherbina, Maxim A.; Chvalun, Sergei N.; Grodd, Linda; Grigorian, Souren; Ameri, Tayebeh; Ponomarenko, Sergei A.; Brabec, Christoph J.
<x xml:space="preserve">Abstract</x> Length of the terminal alkyl chains at dicyanovinyl (DCV) groups of two dithienosilole (DTS) containing small molecules (DTS(Oct)2‐(2T‐DCV‐Me)2 and DTS(Oct)2‐(2T‐DCV‐Hex)2) is investigated to evaluate how this affects the molecular solubility and blend morphology as well as their performance in bulk heterojunction organic solar cells (OSCs). While the DTS(Oct)2‐(2T‐DCV‐Me)2 (a solubility of 5 mg mL−1) system exhibits both high short circuit current density (Jsc) and high fill factor, the DTS(Oct)2‐(2T‐DCV‐Hex)2 (a solubility of 24 mg mL−1) system in contrast suffers from a poor blend morphology as examined by atomic force morphology and grazing incidence X‐ray scattering measurements, which limit the photovoltaic properties. The charge generation, transport, and recombination dynamics associated with the limited device performance are investigated for both systems. Nongeminate recombination losses in DTS(Oct)2‐(2T‐DCV‐Hex)2 system are demonstrated to be significant by combining space charge limited current analysis and light intensity dependence of current–voltage characteristics in combination with photogenerated charge carrier extraction by linearly increasing voltage and transient photovoltage measurements. DTS(Oct)2‐(2T‐DCV‐Me)2 in contrast performs nearly ideal with no evidence of nongeminate recombination, space charge effects, or mobility limitation. These results demonstrate the importance of alkyl chain engineering for solution‐processed OSCs based on small molecules as an essential design tool to overcome transport limitations.